2004
DOI: 10.1111/j.1365-2141.2004.04951.x
|View full text |Cite
|
Sign up to set email alerts
|

Infused CD34+ cell dose, but not tumour cell content of peripheral blood progenitor cell grafts, predicts clinical outcome in patients with diffuse large B‐cell lymphoma and follicular lymphoma grade 3 treated with high‐dose therapy

Abstract: Summary Previously, we have shown that patients with diffuse large B‐cell lymphoma (DLBCL) transplanted with contaminated bone marrow (BM) generally have a poor outcome. Whether this is also the case when peripheral blood progenitor cell (PBPC) grafts are used is not known. Forty‐three patients with chemosensitive DLBCL or follicular lymphoma grade 3 (FLgr3) were treated with high‐dose therapy (HDT) and autologous stem cell support. Nine patients received purged grafts. Quantitative real‐time polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 42 publications
4
43
0
1
Order By: Relevance
“…The outcome of the patients receiving in vitro purged PBPC grafts was inferior compared to the survival of patients with untreated grafts. The limited number of patients receiving purged grafts precludes firm conclusions regarding the impact of this procedure on outcome, although the lack of benefit from purging has also been reported by others (Williams et al, 1996;Bierman et al, 2003;Schouten et al, 2003;Blystad et al, 2004). As the time to neutrophil recovery and the leucocyte/lymphocyte counts at 14 d and 3 months following infusion of CD34 + cells did not differ statistically between in vitro purged and non-purged cases, impaired or delayed engraftment could not be established as an explanation for the different outcomes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The outcome of the patients receiving in vitro purged PBPC grafts was inferior compared to the survival of patients with untreated grafts. The limited number of patients receiving purged grafts precludes firm conclusions regarding the impact of this procedure on outcome, although the lack of benefit from purging has also been reported by others (Williams et al, 1996;Bierman et al, 2003;Schouten et al, 2003;Blystad et al, 2004). As the time to neutrophil recovery and the leucocyte/lymphocyte counts at 14 d and 3 months following infusion of CD34 + cells did not differ statistically between in vitro purged and non-purged cases, impaired or delayed engraftment could not be established as an explanation for the different outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…Patients were eligible for in vitro purging if the amount of harvested PBPC allowed conservation of ‡2 · 10 6 CD34 + cells/ kg as a backup (the total yield had to exceed 4 · 10 6 CD34 + cells/kg); otherwise unmanipulated PBPC were used. In vitro purging was abandoned during the study period when results from other studies (Williams et al, 1996;Bierman et al, 2003;Schouten et al, 2003;Blystad et al, 2004) showed no or limited benefit from in vitro purging for the outcome of HDT in nonHodgkin lymphomas. Poor mobilization was defined as either failure to mobilize >0AE01 · 10 9 cells/L in peripheral blood or failure to achieve ‡2 · 10 6 CD34 + cells/kg body weight from repeated leukaphaeresis.…”
Section: Treatments and Response Assessmentmentioning
confidence: 99%
“…16,17 The ability to mobilize greater numbers of CD34 þ cells may provide more opportunities to deliver optimal cell doses at transplant with faster engraftment and, potentially, better longterm outcomes. 30,43,44 Increased CD34 þ cell yield, in addition, may allow cells to be stored for tandem or salvage transplantation, avoiding the need to attempt mobilization at a time when mobilization could be challenging for the patient.…”
Section: Methods Benefits Limitationsmentioning
confidence: 99%
“…The clinical significance of tumor cell mobilization is unclear, however, and may not affect long-term outcomes. 29,30 Data indicate that tumor cell contamination is not evident, or not significantly increased, following plerixafor treatment, compared with G-CSF alone, in MM and NHL patients. 31,32 However, increased circulating tumor cells have been reported in acute myelogenous leukemia and plasma cell leukemia patients.…”
mentioning
confidence: 99%
“…However, evidence is accumulating from treatment of haematological malignancies that higher doses of HSC can promote faster platelet engraftment and are associated with better overall survival 91,92,93 . Consequently, a dose of 5 × 10 6 CD34 + cells/kg is currently defined as optimal 94,95 .…”
Section: [H3] Autologous Hsc Enrichment and Dosementioning
confidence: 99%